Pengaruh Penggunaan Handphone Berbasis Android Terhadap Aktivitas Belajar Siswa di SD NEGERI 107826 Pematang Sijonam - Eka Nadia Aprilia; Arrini Shabrina Anshor (PGSD UMN Al-Washliyah, 2021)
Advances in the era of technology produce various sophisticated communication tools and at affordable prices. Currently, the most popular means of communication are mobile phones, especially the Android system. In its use, currently all circles of society are able to operate it, be it children to the elderly. SD Negeri 107826 Pematang Sijonam is one of the places affected by these technological advances, this can be seen from the results of initial observations, where many of them are able to operate cellphones. The findings in the field made researchers want to see how the influence of using Android-based cellphones on student learning activities. The method used in this research is correlational quantitative method. With the research subject, namely the fifth grade students of SD Negeri 107826 Pematang Sijonam, totaling 20 students, using saturated sampling technique as a sampling technique. And collecting data taken by using a questionnaire (questionnaire). Keywords: Mobile, android, learning activities.